ZUHUD TAPI KAYA DALAM PERSPEKTIF HADIS - Eko Siswanto (Al-Bukhari : Jurnal Ilmu Hadis, 2018)
This paper talks about Zuhud. Zuhud is the noble nature of believers because it is not deceived by the world with all the delights whether the property, women, and thrones. Zuhud does not mean leaving the world. However, the believer and people who do good deeds in the world, prospering the earth, and doing for the benefit, then achieve the results in the world in the form of halal facilities and pleasures in the world. Imam Al-Ghazali said there were 3 signs of zuhud. Firstly, not happy with what was and not sad because of things that were lost. Secondly, it is the same side of the person who denounces and denounces it, both in relation to property and position. Thirdly, it should always be with God and his heart is dominated by the deliciousness of obedience. Since the heart cannot be free from love, whether it is love for God or love for the world. Zuhud in life was modeled by his companions, such as Abu Bakr, Umar, Uthman bin Affan, and Abdurrahman bin Auf. They are some friends who are wealthy, but do not take all their wealth for themselves and their families.